Methods of selecting industries for depressed areas : an introduction to feasibility studies - Klaassen, Leo H. (Paris : organization for economic co-operation and developemnt, 1967)
This report explore relevant methods to use in the area of industrialization policy. The study focused is mainly upon the role of the local authorities in area (re) development.
include appendix
asm; 16/04/19
Loans
Keywords: Industrial location